An implementation of natural language user interface in smart home system / Ngoi Se Keng - Ngoi , Se Keng (2010)
Smart Home System has facilitated the control of home appliances through computer system. However, the physical interactions between the user and existing graphical user interface such as pointing and clicking button could be a challenge to elderly, whom are generally having vision and motor impairment. This project specifically focuses on the development of a user interface that does not require physical interaction. In this regard, a prototype smart home system namely Natural Language Instruction Driven System (NLIDS) that employed natural language (speech) based user interface has been developed. The prototype system consists of three modules, which are Input & Response Module, Language Processing Module, and Visualization Module. Generally, Input & Response Module is responsible for receive speech instruction as well as provide response to user; Language Processing Module applies business logic to the received instruction; Visualization Module simulates the result of an instruction in computer animation. This project had successfully integrated several state-of-the art technologies and tools such as Java Speech Application Programming Interface, LinkGrammar, JavaJD, WordNet in the development of prototype system. The evaluation carried out at the end of the development shows that the participants in the evaluation are believe that natural language (speech) interface is easier to use, easier to remember, and easier to learn than the graphical user interface.